2021
DOI: 10.1248/bpb.b20-00961
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Selectivity of Aryl Hydrocarbon Receptor (AHR) Agonists towards AHR-Dependent Suppression of Mammosphere Formation and Gene Transcription in Human Breast Cancer Cells

Abstract: We had previously reported that treatment with the aryl hydrocarbon receptor (AHR) agonist β-naphthoflavone (βNF) suppressed mammosphere formation derived from cancer stem cells in human breast cancer MCF-7 cells (Cancer Lett., 317, 2012, Zhao et al.). Here, using several AHR agonists, we have investigated the association of this suppression with the classical ability to induce AHR-mediated gene transcription in the xenobiotic response element (XRE). The mammosphere formation assays were performed using wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…We reported that ligand-activated AhR suppressed tumorsphere (mammosphere) formation in MCF-7 cells. [2][3][4][5] On the other hand, we also found that AhR promoted cell migration and mammosphere formation in human epidermal growth factor receptor 2 overexpressing breast cancer cell lines. 6,7) In addition, AhR is involved in doxorubicin resistance in MDA-MB-231 cells.…”
Section: Introductionmentioning
confidence: 49%
“…We reported that ligand-activated AhR suppressed tumorsphere (mammosphere) formation in MCF-7 cells. [2][3][4][5] On the other hand, we also found that AhR promoted cell migration and mammosphere formation in human epidermal growth factor receptor 2 overexpressing breast cancer cell lines. 6,7) In addition, AhR is involved in doxorubicin resistance in MDA-MB-231 cells.…”
Section: Introductionmentioning
confidence: 49%
“…Agonist-mediated AHR activation represses mammosphere formation and reduces the ALDH-high population, suggesting the repressive effects of AHR on breast CSCs [ 47 , 48 , 49 , 50 ]. Moreover, we have previously reported the suppressive effect of AHR (depending on the agonist used) on mammosphere formation in BC cells [ 22 , 51 ]. These results suggest that AHR has both pro- and anti-tumorigenic activities in cancers and that an agonist can determine its activity.…”
Section: Discussionmentioning
confidence: 99%
“…The mammosphere formation assay was performed as previously described [ 22 ]. Cells were seeded into 96-well ultra-low adherent plates at 1000 cells/well in MammoCult™ Medium (StemCell Technologies, Vancouver, Canada) and cultured for 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations